Multiplex Reverse Transcription-Polymerase Chain Reaction untuk Deteksi Cepat Virus Flu Burung H5N1 (MULTIPLEX REVERSE TRANSCRIPTION-POLYMERASE CHAIN REACTION FOR RAPID DETECTION OF H5N1 AVIAN INFLUENZA VIRUS) - Wasito, Raden; Wuryastuty, Hastari; Tjahyowati, Gesit; Irianingsih, Sri Handayani; Tyasasmaya, Tisna (Jurnal Veteriner; Vol 16 No 1 (2015), 2015)
Avian influenza virus subtype H5N1 (AIV H5N1) is highly pathogenic and fatal in poultry. The virusis still endemic with low virulence rate, although it may play a critical role in causing high morbidity andmortality rates in poultry in Indonesia. In general, diagnostic approach for AIV H5N1 is based onconventional serological and viral isolation methods that have the potential to produce consumings oftime and relatively expensive cost within the laboratory without compromising test utility. Thus, amolecular approach of multiplex reverse transcription-polymerase chain reaction (mRT-PCR) was developedand applied for the detection of matrix gene type A influenza viruses, AIV subtype subtype H5hemagglutinin gene with simultaneous detection of N1 nucleoprotein gene. Thirty sera specimens fromthe diseased commercial chickens that were specifically amplified positive-RT-PCR for AIV H5N1 wereselected for mRT-PCR. The mRT-PCR products were visualized by agarose gel electrophoresis and consistedof DNA fragments of AIV of 245 bp, 545 bp and 343 bp for M, H5 and N1 genes, respectively. Thus, themRT-PCR that can rapidly differentiate simultaneously between these genes is very important for thecontrol and even eradication of AIV transmission in poultry in Indonesia.
Keywords: mRT-PCR, subtype H5N1, commercial chickens, 545 bp gen H5, 343 bp gen N1